(untitled) (Revista horizonte, 2021)
TheÂ Â transformationÂ Â processesÂ Â sufferedÂ Â inÂ Â ChileÂ Â dueÂ Â toÂ Â modernizationÂ Â haveÂ Â broughtÂ Â withÂ Â itÂ Â problems associated with food, nutritionÂ Â and physical activity aspects. These factors and bad habitsÂ Â such as sedentary lifestyle,Â Â impactÂ Â onÂ Â healthÂ Â problems,Â Â epidemiologicalÂ Â andÂ Â aspectsÂ Â relatedÂ Â toÂ Â theÂ Â performanceÂ Â orÂ Â learningÂ Â of the school population. The challenges of national country policy are focused on reducing economic gaps and achievingÂ Â equityÂ Â inÂ Â educationalÂ Â issuesÂ Â asÂ Â promotersÂ Â ofÂ Â socialÂ Â transformation.Â Â TheÂ Â investigationÂ Â ofÂ Â teaching methodsÂ Â toÂ improveÂ Â theÂ Â learningÂ Â orÂ Â academicÂ Â performanceÂ Â ofÂ Â childrenÂ Â is important.Â Â ResearchÂ Â focusedÂ Â on food,Â Â nutritionÂ Â andÂ Â physicalÂ Â activityÂ Â aspectsÂ Â haveÂ Â shownÂ Â theirÂ Â influenceÂ Â onÂ Â the willingnessÂ Â toÂ Â studyÂ Â and modifierÂ Â ofÂ Â neuronalÂ Â chemicalÂ Â environmentsÂ Â thatÂ Â favorÂ Â cognitiveÂ processesÂ Â relatedÂ Â toÂ Â learning.Â Â The articulationÂ Â ofÂ Â variablesÂ Â canÂ Â beÂ Â helpfulÂ Â forÂ Â theÂ transformationÂ Â process.Â